The effect of dentifrice quantity and toothbrushing behaviour on oral delivery and retention of fluoride in vivo. (December 2013) - Creeth, Jonathan; Zero, Domenick; Mau, Melissa; Bosma, Mary Lynn; Butler, Andrew
Abstract : While toothpaste F − concentration and rinsing regimen have well‐characterised impacts on fluoride's effectiveness, other aspects of brushing regimen have much less well‐established effects, in particular, dentifrice quantity and brushing duration. An in vivo study ( n = 42) of oral fluoride delivery (i.e. oral disposition post‐brushing), and retention (i.e. concentration of F − in saliva post‐brushing, a known efficacy predictor), was performed to compare effects observed with those of dentifrice F − concentration and rinsing regimen. Subjects brushed with a NaF‐silica dentifrice (Aquafresh Advanced, 1, 150 ppm F − ) or a control dentifrice (250 ppm F −, same base), for 45, 60, 120 or 180 seconds with 0.5 or 1.5 g dentifrice, and rinsed with 15 ml water once or three times in a cross‐over design. The F − concentration was measured in post‐brushing expectorate, rinse and toothbrush washing samples, and in saliva between 5–120 minutes after brushing. Using 1.5 g versus 0.5 g dentifrice increased F − in all samples: oral retention of F − was almost doubled by this increase. Increasing duration of brushing had more complex effects. The amount of F − in the expectorate increased but decreased in both rinse and toothbrush washing samples. Oral F − retention increased, but only in the period 30–120 minutes after brushing. Over the ranges investigated, the order of importance on oral F − retention was: dentifrice F − concentration > quantity > rinsing regimen > brushing duration. Hence, increasing dentifrice quantity and, to a lesser extent, the duration of brushing, can elevate oral fluoride post‐brushing. Evidence is accumulating that the importance of these variables to fluoride efficacy may have been underestimated.